Development of Lightweight Geopolymer Concrete: Strength and Density Studied (Journal of University of Babylon for Engineering Sciences, 2023)
Geopolymer is a promising alterative of the ordinary Portland cement (OPC). The aim of this study is to prepared lightweight geopolymer concrete by using crumb rubber as aggregate. Sodium silicate solution and sodium hydroxide were used to prepare the alkali activator solution, kaolin was used as a source of the solid part of the geopolymer paste. Crumb rubber was used as partial replacement (5, 10, 15%) by volume of aggregate to produce of lightweight geopolymer concrete. To enhance the bond strength between crumb rubber and geopolymer paste, the crumb rubber was treated with Maliec Anhydride (MAn).The alkali solution was subjected to heat treatment, the effect of the SiO2/Al2O3 ratio, and amount of water were investigated, also, the impact of waste rubber on the mechanical characteristics (compressive strength, flexural strength) and physical properties (density, water absorption and porosity) of lightweight geopolymer concrete were investigated.This study shows that the heat treatment is important to achieve high compressive strength; a strength of 117 MPa was obtained using a ratio of SiO2/Al2O3 of 3.6 and 8 ml of water for geopolymer paste. A compressive strength of 60.6 MPa and flexural strength of 6.076 MPa were obtained for a geopolymer concrete with 554.4 kg and 1293.6 kg fine and course aggregate respectively. Also, the experimental results showed that the strengths and density of lightweight geopolymer concrete were decreased with the increase of waste rubber content. The reduction in weight was about 100 kg per cubic meter for lightweight geopolymer concrete compared with the geopolymer concrete and 300 kg as compared with OPC concrete.